Rice Seasoning (Furikake) using Indigenous Vegetables - Dequiña, Jenefer; Peñalber, Martina (International Journal of Sustainability and Advanced Integrated Research, 2026)
This study aimed to develop and evaluate rice seasoning (furikake) using indigenous vegetables to enhance nutritional quality, sensory acceptability, shelf-life stability, and economic feasibility. Grounded in the concept of functional foods, the study employed an experimental research design with five formulations (F0–F4) using varying proportions of malunggay, amaranth, violet sweet potato leaves, and blue ternate combined with other ingredients. Sensory evaluation was conducted using a 9-point Hedonic Scale among 75 panelists arranged in a Randomized Complete Block Design (RCBD), while proximate analysis determined nutritional composition. Data were analyzed using Analysis of Variance (ANOVA) and Tukey’s Honestly Significant Difference (HSD) test, alongside cost and return analysis. Results showed that increasing indigenous vegetable content improved nutritional composition, with higher protein, dietary fiber, and mineral content, and reduced moisture, fat, carbohydrate, and caloric levels. All formulations were generally well accepted, with formulation F1 obtaining the highest ratings across sensory attributes and overall acceptability, while F4 exhibited the highest nutritional density. Shelf-life evaluation indicated stable product quality with no spoilage over the observation period. Economic analysis revealed decreasing production costs and increasing profitability with higher vegetable incorporation, although F1 provided the best balance between consumer preference and cost efficiency. The study concluded that indigenous vegetable-based rice seasoning is a nutrient-dense, low-calorie, and consumer-acceptable functional food with potential for commercialization, and recommended further testing on microbial stability, extended shelf life, and market feasibility. The study aligns with SDG 2 (Zero Hunger), SDG 3 (Good Health and Well-Being), SDG 12 (Responsible Consumption and Production), and SDG 15 (Life on Land) by promoting nutrient-enriched food products, improving dietary quality, and utilizing locally available resources. It contributes to socio-economic, agricultural, and public health sustainability by supporting local food systems, enhancing nutrition, and promoting affordable, community-based food innovations.